Buitengesloten maar niet afwezig: het aandeel van vrouwen in de beginfase van het oud-katholicisme in Duitsland - Berlis, Angela (Proeven van vrouwenstudies theologie ; deel IV, 1996)
Angela Berlis searches for the 'Old Catholic mothers' in nineteenth-century Germany. Up to now women seem to have hardly figured in the historiography of the origin and the early stages of the Old Catholic movement. What was the actual part played by women in the formation and consolidation of the Old Catholic church in Germany? In order to answer this question it is necessary, according to Berlis, to picture the specific life context of women in those days. She shows how the limited rights of women within the then developing Old Catholic church result from the legal status of women in the German Empire. Over against this exclusion on the formal level she adduces data about the actual presence and activities of women in parishes and institutions, which, to a large extent, she has obtained from her research in archives. The participation of women in the Old Catholic gatherings was made possible in informal ways, whereby women were indeed in a position to set their stamp on the Old Catholic parish life. Moreover, within the scope of public activities permitted to women, some of them used their own financial and professional means and contacts to establish and support Old Catholic (women's) networks.